Pengaruh Sistem Informasi Akuntansi Terhadap Kinerja Karyawan Pada PT. BPRS Lantabur Tebuireng Jombang - Wiwik Sriwahyuni (JFAS : Journal of Finance and Accounting Studies, 2020)
Every organization strives to always improve performance. This encourages companies to utilize accounting information systems in carrying out daily activities. The application of information systems within the organization can simplify and speed up the completion of tasks by each individual. This study aims to determine how the influence of accounting information systems on employee performance. This type of research is quantitative, the population in this study were all employees of PT. BPRS Lantabur Tebuireng in the district of Jombang totaling 31 respondents. Sampling using a saturated sample technique. While data analysis uses simple regression analysis techniques. The results of this study state that the accounting information system has a positive influence on employee performance, so the better the accounting information system, the more employee performance will increase in the company.